THE EFFECTS OF THE DEVELOPMENT OF NATIONAL EDUCATIONAL KOMPETENTSIYALARINI FACTORS TO REALIZE THE SELF ETIVCHI - Rakhimov Babur Baxodirovich (Western European Studies, 2024)
read to realize the self in the present article to improve national kompetentsiyalarini factors affecting k ompeten tsiyaviy education of the subjects of pedagogical approach-ensures the quality of the psychological, but also, probably, you know, will help to maintain the skills and skills . National to realize the self, mh-compassion, tolerance, patriotism, social teachers is high human qualities such as loyalty is necessary
Keywords: reader; spirituality; culture